1991
DOI: 10.1037/0882-7974.6.3.392
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of burden in spouse caregivers of individuals with Alzheimer's disease.

Abstract: This study used the following model of distress: Distress = [Exposure to Stress + Vulnerability]/[Psychological and Social Resources]. The constructs in the model were operationalized as (a) distress in response to caregiver experiences (burden); (b) exposure to stress (care recipient functional impairment in activities of daily living [ADLs]); (c) vulnerability (caregiver health problems, anger, and anxiety); and (d) resources (coping, outlook on life, and social supports). Long-term burden (15-18 months afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
170
3
20

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(203 citation statements)
references
References 41 publications
(74 reference statements)
10
170
3
20
Order By: Relevance
“…For instance, caregiver burden itself is positively related to the degree of patient disability (18). Additionally, supportive responses of the partner or caregiver are related to the functional (dis)ability of the patient (19,20). Higher levels of disability tend to be related to increased partner supportive behaviors (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, caregiver burden itself is positively related to the degree of patient disability (18). Additionally, supportive responses of the partner or caregiver are related to the functional (dis)ability of the patient (19,20). Higher levels of disability tend to be related to increased partner supportive behaviors (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that providing assistance with both ADLs such as bathing and toileting (Vitaliano, Russo, Young, Teri, & Maiuro et al, 1991), as well as IADLs such as errands or transportation (Gonzalez-Salvador, Arango, Lyketsos, & Barba, 1999) can increase caregiver distress (Weitzner et al, 1999).…”
Section: Correlates Of Caregiver Distressmentioning
confidence: 99%
“…The burden the caregiver feels on the face of the symptoms has a positive correlation to the severity of disability 34 . Similarly, supportive behaviors of the partner who, in most situations, also acts as the caregiver directly influence the functional disability of the patient 35,36 . Partner's over-supportive and protective behaviors might result in higher levels of disability 33,37 .…”
Section: Discussionmentioning
confidence: 99%